DESIGN AND CONSTRUCTION OF SALT PRODUCTION MONITORING SYSTEM IN GREENHOUSE BASED ON INTERNET OF THINGS - Aditya Novandi; Desnanjaya, I Gusti Made Ngurah; Sudiarsa, I Wayan; Adnyana, I Gede; Hartawan, I Nyoman Buda (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Karangasem Regency, located in the eastern part of Bali Island, Indonesia, is known for its rich natural and cultural wealth. Traditional salt production in this area is highly influenced by the weather, especially during the rainy season, which hampers the drying process. The use of greenhouses has become an alternative solution, but monitoring temperature, humidity, and light intensity is still done manually, making it inefficient. This study designs and implements an Internet of Things (IoT)-based monitoring system using an ESP32 microcontroller, DHT22 sensors to measure temperature and humidity, and BH1750 sensors for light intensity. The data obtained is displayed in real-time on an LCD screen in the greenhouse and an Android application, enabling more efficient remote monitoring. Based on testing, the system recorded an average temperature of 44.1°C, humidity of 37.2%, and light intensity of 1581.2 lux. These results show that the system operates optimally in supporting the salt production process by providing accurate data to maintain the stability of the greenhouse environment, thus improving the quality and efficiency of salt production.